Dietary inference from dental topographic analysis of feeding tools in diverse animals. Issue 7 (15th March 2022) - Stockey, Christopher; Adams, Neil F.; Harvey, Thomas H. P.; Donoghue, Philip C. J.; Purnell, Mark A.
Abstract: Understanding the relationship between form, function and diet in feeding structures is critical to constraining the roles of organisms in their ecosystem and adaptive responses to food resources. Yet, analysis of this relationship in invertebrates has been hampered by a reliance on descriptive and qualitative characterisation of the shapes of feeding structures. This has led to a lack of robust statistical analyses and overreliance on analogy and plausibility, especially for extinct taxa and animals that are hard to observe feeding. Here we test the efficacy of dental topographic metrics in quantification of form in invertebrate mandibles and assess their relationship with diet. Specifically, we analyse the mandibles of 45 species of extant orthopterans. Orthopterans' well‐constrained diets make them an ideal model system for our study. We find that topographic metrics applied to Orthoptera successfully recover the same relationship between dietary intractability and dental tool morphology as they do in mammals, and that combination of individual metrics in multivariate analysis most strongly captures this relationship. Furthermore, multivariate topographic metrics calibrated to the food consumed by mammals accurately predict dietary differences between orthopterans (82% taxa correctly assigned). Our results demonstrate that these metrics can be used in quantitative analysis and comparison of non‐homologous mouthparts to reliably investigate the relationship between diet, form and function of feeding tools across Bilateria. We anticipate that this will facilitate more rigorous ecological analysis of fossil and historical material, providing new methods to investigate adaptive responses and community‐level interactions through time.